Gastrointestinal Dysfunctions Are Associated with IL-10 Variants in Parkinson's Disease. (5th December 2018) - Shu, Li; Liang, Dongxiao; Pan, Hongxu; Xu, Qian; Yan, Xinxiang; Tang, Beisha; Sun, Qiying
Abstract : Inflammation has been demonstrated to be involved in Parkinson's disease (PD) pathogenesis. There were evidences that the disturbance of the protective function of IL-10 gene contributed to PD. In our study, haplotype analyses were conducted of IL-10 rs1800871 and rs1800872 on 371 PD patients. Because the two SNPs exposed significant linkage disequilibrium demonstrated by Haploview software, we included 177 carriers of both rs1800871 and rs1800872 and 190 noncarriers in clinical phenotype analyses. As to nonmotor symptoms, the score of the gastrointestinal dysfunction domain in Nonmotor Symptom Scale (NMSS) was lower in the carrier group of both SNPs than in the noncarrier group in PD patients (SC: −0.198, p :0. 023 ). Other nonmotor symptoms reflected by relevant rating scales showed negative results. As to comorbidity, no significant statistical significance was observed between the two SNPs and Charlson Comorbidity Index (CCI). In conclusion, we found less severe gastrointestinal dysfunctions of both IL-10 rs1800871 and rs1800872 carriers than noncarriers in PD.